2021
DOI: 10.7189/11.15002
|View full text |Cite
|
Sign up to set email alerts
|

Setting priorities for ageing research in Africa: A systematic mapping review of 512 studies from sub-Saharan Africa

Abstract: Background In 2040, the older population's growth rate in sub-Saharan Africa (SSA) will be faster than those experienced by developed nations since 1950. In preparation for this growth, the National Institute on Aging commissioned the National Academies' Committee on Population to organize a workshop on advancing aging research in Africa. This meeting provided a platform for discussing some areas requiring improvement in aging research in SSA regions. We believed that conducting a systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…Data Extraction. Data extraction was done using an adapted form from a previous review by Kalu et al (2021) but was modified to suit the research questions. The following information was extracted: authors name(s), year of publication, the country study was conducted, study aims/research questions/ hypothesis, the study settings, type of study (qualitative, quantitative, or mixed-method), study design, sampling method, participants characteristics (e.g., the number of participants, mean age of the participants, sex/gender), study themes (if qualitative), study findings (if quantitative or mixed-method), policy statements, clinical implication statements, and future research statement.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Data Extraction. Data extraction was done using an adapted form from a previous review by Kalu et al (2021) but was modified to suit the research questions. The following information was extracted: authors name(s), year of publication, the country study was conducted, study aims/research questions/ hypothesis, the study settings, type of study (qualitative, quantitative, or mixed-method), study design, sampling method, participants characteristics (e.g., the number of participants, mean age of the participants, sex/gender), study themes (if qualitative), study findings (if quantitative or mixed-method), policy statements, clinical implication statements, and future research statement.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…11,12 These reasons are further influenced by the lack of conviction that old-age-related health should be a priority in the context of diverse, pressing public health needs for women and children that currently account for the highest proportion of the population for most African nations. 13 Not placing older adults as a priority group in some African countries adds even more challenges to the already existing issues regarding vaccination, such as accessibility and acceptance. The primary objective of this review was to map the existing literature concerning the 5As-acceptability, accessibility, affordability, awareness, and activation of the COVID-19 vaccination-among adults 55 years and older in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Last, it is expected that the availability of data on older adults will lead to better representation in studies and publications. A systematic review to map the trend and types of research on aging in sub-Saharan Africa showed a slow growth in the number of peer-reviewed studies on older adults in the 80s and 90s and a more rapid increase in the past decade focusing mainly on HIV/AIDS and noncommunicable diseases (NCDs), with majority of the studies concentrated in South Africa followed by Nigeria and Ghana ( Kalu et al, 2021 ). The bulk of the studies were cross-sectional involving small nonrepresentative samples whereas longitudinal studies were much fewer albeit still marred by a lack of large-scale representative samples.…”
Section: Background and Objectivesmentioning
confidence: 99%